Accuracy of SCATT optoelectronic shooting system - Zanevskyy, I.; Korostylova, Y.; Mykhaylov, V. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2014)
This article defines SCATT optoelectronic system accuracy of weapon movement registration. Three types of errors were found in defining the coordinates of the aiming point on a SCATT target: asymmetry of the left to right and up to down results, absolute errors in each direction and the dependence of the error upon the distance to the centre of the target. It was found that the optoelectronic registration shows the biggest errors in the left and up directions from the centre of the target (199%-283%) and relatively less errors in right (54%-188%) and down (18%-188%) directions. In order to make corrections while defining the aiming point coordinates on a SCATT target, one can use the correction factor based on the distance from the aiming point to the centre of the target.